Mycelial growth interactions and mannan-degrading enzyme activities from fungal mixed cultures grown on palm kernel cake - Buchi, Iluyemi Florence; Musa, Mohamed Hanafi (Academic Journals, 2009)
Palm kernel cake (PKC), a by-product of the palm kernel oil extraction process contains mannan as its main polysaccharide. Mixed culture microbial degradation may enhance mannan-degrading enzymes production. Therefore, the objective of the study was to examine the nature of mycelial interactions and corresponding production of mannan-degrading enzymes of PKC. Fungal interactions was carried out using Sclerotium rolfsii and Aspergillus niger co-cultured with three Trichoderma strains (Trichoderma harzianum, Trichoderma longiobrachiatum and Trichoderma koningii) on potato dextrose agar (PDA) in disposable petri-dishes. Measurements of growth diameters were taken on days 2 and 13. For mannan-degrading enzyme production, single and co-cultures of these fungi were carried out under submerged cultivation for 13 days with PKC as the carbon source. About 57% of observed interactions on PDA were deadlock, 29% replacement and 14% intermingling. In Trichoderma sp./A. niger mixed cultures, there was an overall significant enhancement of enzyme: 2 to 200 fold (β-D-mannanase), 8 to 25 fold (β-mannosidase) and from no change to 15 fold increase (α-galactosidase). There was no obvious relationship between enzyme production and protein yield. However, co-culturing of A. niger with the Trichoderma strains showed an enhancement of mannan-degrading enzyme activities without reducing biomass yield.